Enhancing the socio-economic well-being in Egypt by harnessing the capabilities of e-learning programs along with promoting Islamic teachings and values - Ahmad Dahlan, Abdul Rahman; Osama Rashid, Jamilah; Camdzic, Zerina (Eclat Research Publication, 2015)
This work aims to evaluate the implementation of e-learning platforms in schools in Egypt along with promotion of Islamic values. E-learning has been a topic of increasing interest in recent years. In this paper we suggest to combine the areas of e-learning and Web services, by providing electronic learning offerings as (individual or collections of) Web services as well. We elaborate on this by showing how content providers and content consumers (i.e., learners) can communicate appropriately through a Web service platform with its common description, publication, and retrieval functionalities. Since Egypt has been known as a country where many children are not able to have an appropriate education, e-learning platform would provide students with the ability to study even if they live in remote places. Moreover, the integration of new technologies in the classrooms opens new possibilities for the teaching and learning process. Technologies such as a student response system are getting popularity among teachers due to its effects on student learning performance. In this study, our primary objective is to investigate the effect of e-learning platform with combination of Islamic teachings on students learning performance. We also observed the benefits of interactivity between the teacher and the students and among classmates, which positively influences collaborative learning and engagement of students in the class. The results of our study reveal that collaborative learning and engagement of student in the class improves student learning performance. We highly recommend these tools in educational settings to support the learning process.